Preponderant agent, what is that? (Law, State and Telecommunications Review, 2015)
Purpose ”“ Preponderant agent is a new instrument for preventing and reverting adverse impact in competition due to highly concentrated markets. Therefore, this paper's objective is to present and analyze the preponderant agent concept in Mexico with emphasis on the broadcast sector, the telecommunication regulator decisions and the courts' interpretation.Methodology/approach/design ”“ The objectives were achieved by researching and analyzing the main legal documents, the Congress reports and debates, the regulator's decisions and other relevant regulator's documents, as well as final decisions by the courts in connection with broadcast sector.Findings ”“ Among the findings are that certain topics were not duly addressed by the Mexican regulator, or by the Congress, whereas the courts were more willing to hold decisions in favor of public interest based on constitutional intent and deference to the regulator's decision.Originality/value ”“ This paper will be valuable for persons interested in telecommunications, broadcast and antitrust. Although the preponderant agent concept created in Mexico is not necessarily a “best practice”, it does provide an alternative instrument in antitrust. Moreover, the courts decisions also provide criteria regarding regulatory deference for the regulator.